Performance of GPS and Low-cost INS Integration in Marine Surveying - Hide, Christopher; Moore, Terry; Smith, Martin (The International Hydrographic Review, 2004)
The Global Positioning System (GPS) and Inertial Navigation Systems (INS) are increasingly being integrated to obtain robust position and attitude determination solutions. Over the past few years, a number of low cost inertial sensors have come on the market. This article demonstrates the potential performance of an integrated GPS and low cost INS for marine navigation and surveying. It is demonstrated that integrating a low cost INS with a single GPS antenna does not provide the accuracies required. However, using two GPS antennas, such an integrated system can meet marine surveying requirements.